A Broad Study to Develop Maternity Units Design Knowledge Combining Spatial Analysis and Mothers' and Midwives' Perception of the Birth Environment. (October 2022) - Nicoletta, Setola; Eletta, Naldi; Cardinali, Paola; Migliorini, Laura
Objectives: This article investigates how the physical birth environment is perceived by the users (women and midwives) in different settings, a midwife-led unit and an obstetric-led unit, placed in Italy. Background: In the field of birth architecture research, there is a gap in the description of the spatial and physical characteristics of birth environments that impact users' health, specifically for what concerns the perception by women. Methods: The study focuses on multi-centered mixed methods design, employing both quantitative and qualitative research methods (questionnaire, spatial analysis) and covering different disciplines (architecture, environmental psychology, and midwifery). Results: The results revealed significant differences between the two settings and some associations between perceived and spatial data concerning: calm atmosphere, greater intimacy, spacious birth room, clarity of service points, clarity in finding midwives, sufficient space for labor, noise, privacy, and the birth room adaptability. Conclusions: The findings confirm the importance of the spatial layout and indicate documented knowledge as an input to consider when designing birth spaces in order to promote user well-being.